Performance Appraisal 360 Feedback: "Sebuah Pendekatan untuk Menciptakan Competitive Advantage Bagi Organisasi" - Fachrully Rachmayati (Jurnal Manajemen Maranatha, 2006)
The success of organization in managing the performance is determined by appraisal system that can accommodate the organization’s need to create competitive advantage. Organization wants to know how well the human resource performs on their jobs. One of the popular tools today is the performance appraisal 360-degree, which provides a multidirectional measurement scope for employee performance. Using the performance appraisal 3600 feedback, the organization can assess human resource’s performance and behaviour objectively, unbiased, and encouraging the performance improvement. This article identified the different between traditional and3600 feedback performance appraisals in organizations. First, describe the new performance appraisals. Next, examine how to managing the strategy of performance appraisals. Finally, implications for organization are discussed.